ORGANIZATIONAL AND ECONOMIC SITUATION OF ENERGY SYSTEM INFORMATION SECURITY OF ENERGY INDUSTRY ENTERPRISES IN UZBEKISTAN - Koraboev , Eldor Alijonovich (Innovative Development in Educational Activities, 2023)
This manuscript provides an assessment of the organizational and economic status of the cyber security energy system of energy industry enterprises, as well as relevant suggestions and recommendations.